O Estado como garantidor dos direitos fundamentais e o protagonismo do Supremo Tribunal Federal na efetivação dos direitos sociais - Daiuto, Alexandre Alcorta (2018)
The present study aims at examining the State as guarantor of social rights and the role of the Judiciary for its effectiveness.The Constitutional State of Law guarantees the effectiveness of fundamental rights through the independent and harmonious performance of its Powers. The independence and harmony between the Powers characterizes a system of checks and balances multifaceted, modulated and interrelated, aimed at the realization of the rights guaranteed by the State. From the balance equated between the Powers of the State arises the efficient mechanism for the realization of rights. On the other hand, the imbalance of this system, due to the disharmony between the activities and functions of the State, frustrates the realization of rights, creating a space for the Judiciary, especially the Supreme Court, to act as guarantor of the Constitution, becoming protagonist in its effectiveness. It is intended with this reflection to investigate the duty of the State to guarantee the effectiveness of social rights and the role of the Judiciary in this regard. The research was performed using the deductive method combined with bibliographical research and documentary research, allowing the scope and depth of the theme established within the limits researched.